Impact of the COVID-19 Pandemic on the Work Activity of Spanish Physical Therapists and Their Response to Vaccination - Montero-Navarro, Sergio; Sánchez-Más, Jesús; Salar-Andreu, Cristina; Molina-Payá, Francisco Javier; Orts-Ruiz, Cristina; Botella-Rico, José Martin; Tuells, José; Rodríguez-Blanco, Noelia (Frontiers in Public Health, 2022)
Due to the COVID-19 pandemic, physical therapists have had to adopt a set of specific protection measures, which have had an impact on their clinical activity and economy. The objective was to evaluate the impact of the COVID-19 pandemic on the work of Spanish physical therapists, as well as their attitudes and predisposition to vaccination. An online questionnaire was divided into five sections: 1) demographic and professional data; 2) labor impact; 3) precautions and infection-control measures; 4) economic impact; and 5) vaccine acceptance and adverse effects. Of the 666 participants, 62.1% showed a reduction in their working hours motivated by: fear of infection (p = 0.007), financial issues (p = 0.002) and being in quarantine or isolation (p <0.001). Of these, 36.4% were forced to close the clinic, 62.7% requested help from the government, but only 12.04% mentioned that it was adequate. The main prevention measures adopted were the use of gels and masks and, in the private sector, disinfection with ozone or ultraviolet light (p <0.05). The acceptance of the vaccine was high, 87.5%, being lower among the group over 40 years of age, self-employed, widowed or separated. More adverse effects were mentioned after receiving the AstraZeneca-Oxford vaccine, compared to Pfizer-BioNTech or Moderna. In conclusion, this study assessed for the first time that the COVID-19 pandemic in Spain had a negative impact on work and finances of physical therapists. The vaccine was widely accepted, in part by the economic impact that an infection in the work setting could signify.